Microbial composite hydrogel as well as preparation method and application thereof

By using PEG-PVA/SA/nano-TiO2 hydrogel carrier to fix Bacillus velezensis microorganisms, the problem of the existing technology being difficult to simultaneously degrade multiple pollutants in food wastewater is solved, efficient and stable pollutant degradation is achieved, and the disadvantages of magnetic materials are avoided.

CN119591256AActive Publication Date: 2025-03-11CHANGSHA FOOD & DRUG INSPECTION INST

Patent Information

Application Number
CN202411739941.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to degrade various pollutants such as COD, TP and tetracycline in food wastewater at the same time, and magnetic materials may cause aggregation and oxidation in water environments, increasing costs.

Method used

The Bacillus velezensis microorganisms were fixed by PEG-PVA/SA/nano-TiO2 hydrogel carrier. Various pollutants in food wastewater were treated through the synergistic effect of hydrogel adsorption, microbial biodegradation, and nano-TiO2 adsorption and antibacterial activity.

Benefits of technology

It has achieved efficient degradation of various pollutants in food wastewater, with higher stability, integration and long-term mechanism, avoiding the disadvantages of magnetic materials, and promoting the recycling of nano-TiO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591256A_ABST
    Figure CN119591256A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of removal of complex pollutants in water, and particularly relates to microbial composite hydrogel as well as a preparation method and application thereof. The microbial composite hydrogel is prepared from the following components in parts by weight: 1 to 3 parts of polyvinyl alcohol, 3 to 8 parts of polyethylene glycol, 2 to 6 parts of sodium alginate, 0.05 to 0.08 part of nano titanium dioxide, 10 to 25 parts of CaCl2, 10 to 25 parts of boric acid, 5 to 15 parts of potassium persulfate and bacillus velezensis, and the concentration of the bacillus velezensis is 0.35 * 10 < 8 > to 0.6 * 10 < 8 > cells / mL. The microbial composite hydrogel can effectively treat various pollutants in wastewater at the same time, has more efficient pollutant degradation capacity and wider application range, and realizes comprehensive integrated treatment of food wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of complex pollutant removal in water bodies, and particularly relates to a microbial composite hydrogel and a preparation method and application thereof. Background Art

[0002] Food wastewater mainly includes high concentrations of organic pollutants, suspended solids and grease, chemicals such as phosphorus and chlorine used for cleaning and disinfection, antibiotics or food additives lost into the water, and nutrient residues such as carbohydrates, proteins and lipids. Direct discharge will seriously pollute the surrounding land and surface water.

[0003] Bacillus velezensis can effectively degrade pollutants in wastewater through microbial decomposition. Immobilized microbial technology can effectively protect microbial cells, increase the contact opportunities between microorganisms and pollutants, and improve the biodegradation ability of microorganisms to organic pollutants. Immobilized carriers can provide a microenvironment for microorganisms, achieve high-density fermentation, promote microbial metabolism, and thus improve wastewater treatment efficiency.

[0004] For example, in order to degrade COD, the prior art fixes Bacillus velez on the surface of sodium alginate (SA) / polyvinyl alcohol (PVA) / nano-zinc oxide (Nano-ZnO) microspheres to prepare SA / PVA / ZnO microspheres. However, the prior art has a single effect on the degradation of organic matter in wastewater, and can only degrade COD, but cannot degrade difficult-to-degrade substances such as tetracycline in wastewater.

[0005] There is another prior art that prepares a magnetic immobilized microbial composite material using Bacillus velez, sodium alginate, nano Fe3S4, and CaCl2. The magnetic immobilized microbial composite material has the ability to degrade tetracycline, but the magnetic material may aggregate and be oxidized in an aqueous environment, reducing its dispersibility and adsorption capacity, and the magnetic material may cause a high cost when used on a large scale. Summary of the invention

[0006] The object of the present invention is to provide a microbial composite hydrogel which can effectively and comprehensively treat various pollutant components in food wastewater without using magnetic materials, a preparation method thereof and an application thereof in treating food wastewater.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A microbial composite hydrogel comprises, by weight, 1-3 parts of polyvinyl alcohol, 3-8 parts of polyethylene glycol, 2-6 parts of sodium alginate, 0.05-0.08 parts of nano titanium dioxide, 10-25 parts of CaCl2, 10-25 parts of boric acid, 5-15 parts of potassium persulfate and Bacillus velezensis, wherein the concentration of Bacillus velezensis is 0.35*10 8 -0.6*10 8 cells / mL.

[0009] In a preferred embodiment, the molecular weight of the polyethylene glycol is 2000-6000.

[0010] In one preferred embodiment, the molecular weight of the polyvinyl alcohol is 20,000-40,000.

[0011] In a preferred embodiment, the nano titanium dioxide is 0.07-0.08 parts.

[0012] In one preferred embodiment, the particle size of the nano titanium dioxide is 60-100 nm, and the nano titanium dioxide is anatase type.

[0013] In one preferred embodiment, the particle size of the nano titanium dioxide is 70-80 nm.

[0014] Bacillus velezensis is the Bacillus velezensis disclosed in the prior art (AJD, AMJ, AYQZ, et al. Enhanced treatment of organic matter in slaughter wastewater through live Bacillus velezensis strain using nano zinc oxide microsphere[J]. 2021).

[0015] Based on the same inventive concept, the present invention also claims a method for preparing the microbial composite hydrogel, comprising the following steps:

[0016] S1, polyvinyl alcohol, polyethylene glycol, sodium alginate, nano titanium dioxide and deionized water are mixed, stirred evenly at 900-100° C., and cooled to obtain a mixed solution 1;

[0017] S2, mixing CaCl2, boric acid and potassium persulfate uniformly to obtain a mixed solution 2;

[0018] S3, dropping the mixed solution 1 into the mixed solution 2 for chemical cross-linking, letting it stand for 6-18 hours after the dropwise addition, then washing with water, freeze-drying, and preparing hydrogel microspheres;

[0019] S4. Mix the hydrogel microspheres and the Bacillus Velez suspension, and culture them at 35-38° C. and 150-220 rpm for 3-6 hours to obtain the microbial composite hydrogel.

[0020] In one preferred embodiment, the concentration of the bacterial suspension is 0.8*10 8 -1.2*10 8 cells / mL.

[0021] In one preferred embodiment, the particle size of the hydrogel microspheres is 2-5 mm.

[0022] Hydrogel microspheres with too large a particle size have a relatively small specific surface area, which reduces the contact area with pollutants and reduces the adsorption efficiency. Hydrogel microspheres with too small a particle size may cause blockage in the wastewater treatment system, affect the permeability of the water flow, and increase the difficulty of recycling and reuse.

[0023] In one of the preferred embodiments, in the microbial composite hydrogel, the hydrogel microspheres are loaded with 35-60% of the bacteria in the Bacillus Velez suspension.

[0024] Based on the same inventive concept, the present invention also claims to protect the use of the microbial composite hydrogel in removing COD, TP and / or tetracycline in wastewater.

[0025] In a preferred embodiment, the wastewater is food wastewater.

[0026] Based on the same inventive concept, the present invention also claims to protect the use of the microbial composite hydrogel in inhibiting microorganisms in wastewater.

[0027] In a preferred embodiment, the microorganism is Escherichia coli and / or Staphylococcus aureus.

[0028] The present invention will be further explained below:

[0029] The invention constructs a novel PEG-PVA / SA / nano-TiO2 hydrogel, and fixes it with Bacillus velezensis separated from wastewater to form a hydrogel microsphere-organic degradation bacteria system. The hydrogel is a three-dimensional flexible polymer network structure and a high molecular material with good hydrophilicity. The hydrogel adsorbent has super strong adsorption capacity, wide pH value independence, low cost and sustainability. Pollutants can be adsorbed on the outer surface of the hydrogel or in the expanded three-dimensional hydrogel network, and then separated from the water body along with the hydrogel. The composition of the hydrogel is crucial to its function. Sodium alginate (SA) is one of the most commonly used matrices, but it is usually fragile and not conducive to adsorption treatment. Mixing SA with polyvinyl alcohol (PVA) can effectively improve the mechanical strength, durability and chemical stability of the hydrogel. Polyethylene glycol (PEG) is a porous agent that can form a porous structure of the hydrogel. The high specific surface area and porous structure of the hydrogel are conducive to absorbing a large amount of pollutants. Nano-titanium dioxide (nano-TiO2) is a low-toxic inert chemical material containing many hydroxyl groups. Nano-TiO2 can be used as an effective absorbent due to its high surface area, porous structure, excellent stability under acidic conditions, environmental friendliness and the presence of a large number of surface absorption sites. Adding nanoparticles to the hydrogel skeleton can improve the mechanical strength, expansion behavior, thermal properties and chemical properties of the hydrogel composite material, thereby increasing the practical practicality and life cycle of the absorbent material and increasing the available absorption sites of the hydrogel system. At the same time, nano-TiO2 can generate electron / hole pairs under natural light conditions and generate reactive oxygen species (ROS) through light absorption. Reactive oxygen can destroy the cell wall of bacteria and the membrane of viruses, thereby producing a certain antibacterial effect. However, Bacillus Velez is also at risk of being killed. Therefore, the present invention effectively inhibits Staphylococcus aureus and Escherichia coli by adjusting the particle size and addition amount of nano-TiO2 without killing Bacillus Velez. The nano-TiO2 powder separated as a hydrogel material after water treatment can be more easily recycled to avoid secondary pollution. Ca 2+ Cross-reaction with the wall material PEG-PVA / SA reduces the solubility of the wall material and promotes the enhancement of the mechanical properties of the hydrogel microspheres. It also accelerates the formation of bacterial extracellular polymers and enhances the cohesion of the microbial surface through c-di-GMP in the signal molecule.

[0030] Due to the synergistic effect of the adsorption of the hydrogel carrier, the biodegradation of the microorganisms, and the adsorption and antibacterial activity of the dititanium nanoparticles, the microbial composite hydrogel of the present invention is able to treat a variety of pollutants in food wastewater and maintain a long-term mechanism.

[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0032] 1. The microbial composite hydrogel of the present invention can comprehensively treat a variety of pollutants in wastewater, has a more efficient pollutant degradation ability and a wider range of applications, realizes the comprehensive and integrated treatment of food wastewater, and can be flexibly adjusted according to changes in pollutant types and concentrations to achieve the best treatment effect.

[0033] 2. The microbial composite hydrogel of the present invention has more stable performance, higher integration, and longer life cycle, and can give full play to the advantages of immobilization technology.

[0034] 3. The nano-TiO2 powder separated by the microbial composite hydrogel of the present invention can be more easily recovered to avoid secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The morphological structure diagram of PEG-PVA / SA / nano-TiO2 microspheres;

[0036] Figure 2 The SEM and FT-IR images of PEG-PVA / SA / nano-TiO2 microspheres; in the figure, (a) is the SEM of nano-TiO2; (b) is the SEM of PEG-PVA / SA microspheres; (c) SEM of PEG-PVA / SA / nano-TiO2 microspheres; (d) FT-IR spectrum;

[0037] Figure 3 The bar graph is the ability of microspheres with different nano-TiO2 contents to immobilize Bacillus velezensis;

[0038] Figure 4 Bar graph showing the physical stability of hydrogel microspheres treated at different temperatures and pH levels;

[0039] Figure 5 It is a curve diagram of the degradation efficiency of organic compounds, phosphorus-containing components and antibiotics in simulated food wastewater by microbial composite hydrogel microspheres; in the figure, a is the biodegradation efficiency of COD, b is the fitting equation of the biodegradation efficiency of COD changing with time, c is the biodegradation efficiency of TP, d is the fitting equation of the biodegradation efficiency of TP changing with time, e is the biodegradation efficiency of tetracycline, and f is the fitting equation of the biodegradation efficiency of tetracycline changing with time. DETAILED DESCRIPTION

[0040] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention by adopting other various specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made by adopting the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict. The molecular weight of the polyethylene glycol used in the embodiments of the present invention is 2000. The molecular weight of the polyvinyl alcohol is 20,000.

[0041] Example 1

[0042] Preparation of microspheres

[0043] Solution 1 is 1.0wt% PVA (polyvinyl alcohol), 3.0wt% PEG polyethylene glycol 2000 and 2.0wt% SA sodium alginate dissolved in deionized water, stirred continuously at 95°C for 15 minutes, and then 0-2.0g / L of nano-TiO2 (particle size 80nm, rutile type) was added and fully dispersed until a milky white gel-like uniform system of 10mL was formed. Solution 2 is 2.0wt% CaCl2, 2.0wt% H3BO3 boric acid and 1.0wt% K2S2O8 potassium persulfate dissolved in deionized water to obtain 50ml of solution 2. After solution 1 was cooled to room temperature, it was aspirated with a syringe and added dropwise to solution 2. After immobilization for 12 hours, hydrogel microspheres containing different concentrations of nano-TiO2 were formed. The microspheres were rinsed three times with sterile water and stored at 4°C.

[0044] The PEG-PVA / SA / nano-TiO2 microspheres were observed visually. Figure 1 As shown. The results show that the hydrogel microspheres containing 0.5g / L nano-TiO2 are elastic, the nano-TiO2 is evenly distributed, the tailing is minimal, the morphology is better, and the operation is less difficult. As the concentration of nano-TiO2 increases, the viscosity of solution 1 increases, resulting in more obvious tailing during the preparation process, poor molding of the prepared material, hard texture, and uneven distribution of nano-TiO2. Poor microsphere morphology will affect the bacterial immobilization effect and the absorption capacity of the carrier, further affecting the degradation of pollutants. At the same time, the Ca in solution 2 2+ It cross-reacted with the wall material PEG-PVA / SA (solution 1), reduced the solubility of the wall material, and promoted the enhancement of the mechanical properties of the hydrogel microspheres.

[0045] The PEG-PVA / SA / nano-TiO2 microspheres were freeze-dried, fixed and gold-sprayed. The microstructure of the microspheres was observed using a scanning electron microscope (SEM, Zeiss Zeiss Sigma 300, Germany) with an acceleration voltage of 3 kV and a magnification of 2000 times.

[0046] Freeze-dried PEG-PVA / SA microspheres (0% nano-TiO2 added), PEG-PVA / SA / nano-TiO2 microspheres and nano-TiO2 powder were ground in an agate mortar and then passed through a 200-mesh sieve. 40 mg of the powder was fixed with KBr as the background and tested with Fourier transform infrared radiation (FT-IR, Thermo Scientific, Germany). The spectrum was recorded in the range of 4000 to 500 cm -1 , resolution 4cm -1 .

[0047] The results are as follows Figure 2 As shown in the figure, (a) is the SEM of nano-TiO2; (b) is the SEM of PEG-PVA / SA microspheres; (c) is the SEM of PEG-PVA / SA / nano-TiO2 microspheres; (d) is the FT-IR spectrum. As can be seen from the figure, a large number of uniformly enlarged pores are formed on the surface of PEG-PVA / SA microspheres, which is conducive to the loading of bacterial strains, the exchange of substances and the absorption of pollutants. The particle size of PEG-PVA / SA microspheres is 5mm (such as Figure 2 b). Figure 2 a and 2c show that the nano-TiO2 in PEG-PVA / SA / nano-TiO2 microspheres is effectively aggregated in the voids on the surface of the microspheres, occupying fewer sites and not affecting the immobilization effect and absorption efficiency.

[0048] FT-IR was performed on nano-TiO2 and hydrogel microspheres to study the functional groups and interactions in the microspheres. Figure 2 PEG-PVA / SA microspheres at 3473 cm -1 The broad peak at 2926 cm-1 is attributed to the stretching vibration of -OH. -1 、1627cm -1 、1402cm -1 and 1096cm -1 The absorption peaks generated at 647 cm-1 correspond to the stretching vibrations of CH, -COO, -CH2- and CO. -1 The broad bands observed on the left and right are the result of the addition of nano-TiO2. The increase in peak width and the lower wavenumber from 3300 cm -1 Slightly moved to 3400cm -1 This indicates that hydrogen bonding is formed between nano-TiO2 and the support. -1The characteristic peaks between the -OH stretching vibrations indicate that nano-TiO2 has been successfully integrated into the hydrogel.

[0049] Example 2

[0050] Preparation of microbial composite hydrogel

[0051] The Bacillus velezensis used in the experiment is a strain that was isolated from slaughterhouse wastewater and can be used to degrade COD. 100 μL of Bacillus velezensis was inoculated into 50 mL of LB liquid culture medium and cultured at 37°C and 180 rpm for 24 hours. Subsequently, the culture solution was transferred to a sterile centrifuge tube and centrifuged at 6000 r / min for 5 minutes. The supernatant was discarded and the centrifuge tube was rinsed with sterile water. This process was repeated three times. Sterile water was added and vortexed to completely suspend the bacteria in the sterile water. The concentration of the bacterial suspension was adjusted so that the OD 600 =1.0 (the concentration of bacterial suspension at this absorbance is about 1.0*10 8 Cells / mL). 6 g of microspheres containing different concentrations of nano-TiO2 were transferred to a conical flask containing 50 mL of the above bacterial suspension. The microspheres were cultured at 37°C and 180 rpm for 4 hours to fix and adsorb Bacillus velezensis. Thus, a microbial composite hydrogel containing different concentrations of nano-TiO2, i.e., a hydrogel microsphere-organic degradation bacteria system, was constructed.

[0052] After 4 hours of microsphere immobilization, the absorbance of the bacterial suspension was measured at 600 nm UV wavelength. The bacterial suspension without microspheres was used as a control. The OD 600 The degree of reduction can determine the ability of the microspheres to fix bacteria. The fixation efficiency of the microspheres on bacteria is calculated as follows:

[0053]

[0054] Where OD0 is the OD of the initial bacterial suspension 600 OD1 is the OD of the bacterial suspension after immobilization 600 .

[0055] By measuring the change in absorbance at 600nm after co-culture of microspheres and bacteria, the carrying rate of microspheres for Bacillus velezensis was obtained, thereby reflecting the immobilization efficiency. The effective immobilization of Bacillus velezensis by microspheres resulted in a decrease in OD value. The results are as follows: Figure 3As shown. The results show that the hydrogel microspheres have a significant carrying capacity for this organic degradable bacteria. When the nano-TiO2 concentration increases from 0g / L to 0.5g / L, the ability of the microspheres to immobilize Bacillus velezensis gradually increases, and the highest bacterial loading rate of 0.5g / L nano-TiO2 microspheres reaches 57.5%. With the continuous increase of nano-TiO2 concentration, the bacterial carrying capacity of the microspheres decreased or had no significant difference.

[0056] The microbial composite hydrogels containing different concentrations were placed on a culture medium coated with Escherichia coli, Staphylococcus aureus and Bacillus Velezii and cultured at 37°C for 24 hours. The antibacterial properties of the microbial composite hydrogel microspheres with different concentrations were determined by measuring the diameter of the inhibition zone. The results are shown in Table 1.

[0057] Table 1 Diameters of different microsphere inhibition zones

[0058]

[0059]

[0060] Note: N / D means no inhibition zone was detected.

[0061] The results are shown in Table 1. When the concentration of nano-TiO2 in the microspheres was 0-0.2 g / L, no inhibition zone was detected. When the concentration was 0.5-0.8 g / L, the microspheres showed inhibition zones for both Escherichia coli and Staphylococcus aureus, but no inhibition zone was detected for Bacillus velezensis. When the concentration increased to 1 g / L and above, the microspheres had an inhibitory effect on all three bacteria, and the diameter of the inhibition zone gradually increased.

[0062] The nano-TiO2 microspheres containing 0.5-0.8g / L showed a significant inhibitory effect on Escherichia coli and a moderate inhibitory effect on Staphylococcus aureus. The inhibitory effect of this concentration of microspheres on Escherichia coli was significantly stronger than that on Staphylococcus aureus, while having little effect on the growth and reproduction of degradable bacteria.

[0063] From the above results, it can be seen that when the nano-TiO2 concentration is 0.5-0.8g / L, the microspheres have better morphology, uniform distribution of nano-TiO2, less difficult operation, and the ability of microspheres to immobilize Bacillus velezensis is the strongest. In addition, the microspheres at this concentration have an inhibitory effect on Escherichia coli and Staphylococcus aureus, and do not affect the growth and reproduction of biodegradable bacteria Bacillus velezensis. Furthermore, when the nano-TiO2 concentration is 0.7-0.8g / L, it is best for Escherichia coli and Staphylococcus aureus, while not inhibiting Bacillus velezensis.

[0064] At the same time, the present invention also adjusts the particle size of nano-TiO2 to 40, 60, 100, and 120nm on the basis of Example 1, and the addition amount is 0.5g / L, and a series of microbial composite hydrogels are prepared. The results show that the microbial composite hydrogel prepared with a particle size of 60-100nm has a good inhibitory effect on Escherichia coli and Staphylococcus aureus. At the same time, the ability of the microbial composite hydrogel prepared under this range to immobilize Bacillus velezensis is relatively good. The specific surface area of ​​nano-TiO2 with too large a particle size is reduced, which reduces the contact area with bacteria, resulting in a reduced ability to penetrate the bacterial cell wall. And nano-TiO2 with too large a particle size is difficult to distribute evenly in the hydrogel, resulting in the instability of the gel structure, affecting the mechanical properties of the gel, and then affecting the overall performance and application effect. Nano-TiO2 with too small a particle size has a large specific surface area, and the van der Waals force and surface energy between the particles increase, resulting in agglomeration. Agglomeration reduces the effective specific surface area of ​​the material, resulting in reduced system stability and adversely affecting the photocatalytic and antibacterial properties.

[0065] The physical stability of the prepared microbial composite hydrogel (nano-titanium dioxide particle size of 80nm, added in an amount of 0.5g / L) was tested: The physical stability of the microspheres at different temperatures and pH values ​​was studied by testing the weight loss rate. A certain mass (m0) of microspheres was weighed and placed in solutions of different pH values ​​(4, 5, 6, 7, 8, 9, 10) and stored at different temperatures (25°C and 4°C). The microspheres were taken out every 5 days and the mass (m i ). The weight loss rate is calculated according to the following formula:

[0066]

[0067] Where m0 is the mass of the microspheres on day 0 (g); mi is the mass of the microspheres on the i-th day of storage (g).

[0068] The results are as follows Figure 4 shown. Figure 4 The changes of weight loss rate of hydrogel microspheres at 4°C and 25°C with pH and time are illustrated. The weight loss rate of hydrogel microspheres in each treatment showed an increasing trend with the increase of storage time. The weight loss rate of hydrogel microspheres at 4°C was generally lower than that at 25°C (p<0.01), indicating that PEG-VA / SA / nano-TiO2 microspheres were more stable at 4°C. After storage at 4°C for 20 days, the weight loss observed under neutral conditions was significantly lower.

[0069] Under the same conditions, the particle size and addition amount of nano-TiO2 also affect the stability. When the particle size of nano-TiO2 is 60-100nm and the addition amount is 0.5-0.8g / L, the stability of the prepared microbial composite hydrogel is the best.

[0070] Example 3

[0071] Comprehensive degradation of food wastewater

[0072] The biodegradability of the hydrogel microsphere-organic degradation bacteria system was studied using simulated wastewater. Ammonium sulfate (300 mg / L) was added to the LB medium to investigate the degradation effect of the microbial composite hydrogel (nano-titanium dioxide particle size of 80nm, added in an amount of 0.5g / L) on COD. Potassium dihydrogen phosphate (100 mg / L) was used to simulate phosphorus pollutants to investigate the degradation effect of the microbial composite hydrogel (nano-titanium dioxide particle size of 80nm, added in an amount of 0.5g / L) on TP. Tetracycline was used as a substitute for antibiotic pollutants to determine the degradation effect of the microbial composite hydrogel (nano-titanium dioxide particle size of 80nm, added in an amount of 0.5g / L) on antibiotics. The hydrogel microsphere-organic degradation bacteria system was added to the simulated wastewater (6g / 50mL simulated wastewater) and cultured at 37°C, 180 rpm, and white light irradiation. Samples were collected every 24 hours. The COD and TP in the simulated wastewater were measured using a water quality analyzer (GL-800, Shandong Geluyi) and supporting reagents, and the degradation rate was calculated. The degradation rate of COD and TP by the system was calculated using the following formula:

[0073]

[0074]

[0075] Among them, COD0 and TP0 are the initial COD values ​​or TP values ​​of the simulated wastewater, and COD1 and TP1 are the COD values ​​or TP values ​​after degradation for a period of time.

[0076] The degradation efficiency of the hydrogel microsphere-organic degrading bacteria system on organic compounds, phosphorus-containing components and antibiotics in simulated food wastewater is shown in Figure 2. Figure 5 As shown in the figure, 5a-5d show that the system has a significant degradation effect on COD and TP, and the degradation rates reach the highest on the 7th day, which are 71.85% and 36.84%, respectively. The degradation rates of COD and TP by the hydrogel without nano-TiO2 are only 35.04% and 19.87%.

[0077] The introduction of tetracycline into bacterial cells will result in the blocking of bacterial peptide chain extension, thus producing an inhibitory effect. Therefore, the critical inhibitory concentration of tetracycline was first studied. Simulated wastewater containing 0, 1.0, 5.0 and 10.0 mg / L tetracycline was prepared, 50 mL of bacterial suspension was added to the simulated wastewater, and the initial OD was measured. 600 After 24 hours of culture, observe the turbidity of the culture medium and measure the OD 600 , compare the inhibition degree of different concentrations of tetracycline on the growth of Bacillus velezensis. Prepare 50mL simulated wastewater with tetracycline, and determine the initial amount of tetracycline based on the ultraviolet absorbance at 357nm. Add the system (6g / 50mL simulated wastewater) to the culture medium and culture, then measure the ultraviolet absorbance at 357nm every 24 hours, and calculate the tetracycline degradation rate.

[0078]

[0079] Where OD0 is the initial OD of the simulated wastewater 357 Value, OD1 is the OD after degradation for a period of time 357 value.

[0080] The results are shown in Table 2.

[0081] Table 2 Inhibitory effect of different concentrations of tetracycline on the growth of Bacillus velezensis

[0082]

[0083] A solution containing 5 g / L tetracycline was selected as the simulated antibiotic wastewater to investigate the degradation effect of the system. Figure 5 e and 5f. The degradation effect and trend of the system on tetracycline were similar, with a degradation rate of 40.52% on the 5th day. The degradation rate of tetracycline by the hydrogel without nano-TiO2 was only 17.33% on the 5th day. The degradation rate of sodium alginate (SA) / polyvinyl alcohol (PVA) / nano zinc oxide (Nano-Zno) microspheres prepared under the optimal conditions (SA 6%, PVA 9%, ZnO 0.015%) of the prior art (AJD, AMJ, AYQZ, et al. Enhanced treatment of organic matter in slaughter wastewater through live Bacillus velezensis strain using nano zinc oxide microsphere[J]. 2021) was only 20.50% on the 5th day for tetracycline.

[0084] Through Figure 5 The results shown in 5a, 5b and 5e are matched to obtain the degradation rate y of COD, TP and TC as a function of time x. The COD degradation rate equation is y = -1.763x 2 +20.915x+6.274. The equation of TP is y=0.432x 2 +6.858x+8.565. The equation of TC is y=-0.772x 2 +9.612x+8.875. The coefficient of determination (R 2 ) are 0.9590, 0.9960 and 0.9898 respectively, indicating that the model explains 95.90%, 99.60% and 98.98% of the degradation rate indicator change information, has good consistency, and can help predict the subsequent degradation rate change over time.

[0085] Due to the combined effects of the adsorption of the hydrogel carrier, the biodegradation of microorganisms, and the adsorption and antibacterial activity of nano-TiO2, the microbial composite hydrogel of the present invention can treat a variety of pollutants in food wastewater and maintain a long-term mechanism. Bacillus velezensis shows strong resistance and can grow and reproduce in wastewater environments with high safety. In particular, Bacillus velezensis shows efficient biodegradation of wastewater. Ca in the microspheres 2+ It may accelerate the formation of bacterial extracellular polymers and enhance the aggregation of microorganisms on the surface through c-di-GMP in the signaling molecule. 2+ It can improve the deposition efficiency in wastewater, regulate the formation of biofilm and promote the attachment growth process. The immobilization of hydrogel promotes the growth of microorganisms and enhances the secretion of a series of bioactive substances. Bacillus velezensis can biologically remove phosphorus, especially in the context of eutrophication of water bodies, it can effectively reduce the phosphorus content of water bodies and improve water quality. PEG-PVA / SA microspheres have good pore changes and biofriendliness, and can effectively absorb pollutants in water environments. Bacillus velezensis cells can grow and biodegrade more continuously on microspheres. PVA improves the mechanical strength, durability and chemical stability of SA hydrogel microspheres. PEG, as a porogen, forms a porous structure of the hydrogel, which can be used for immobilization to obtain excellent mechanical and mass transfer properties. The addition of H3BO3 and K2S2O8 helps to prolong the durability and stability of polyvinyl alcohol hydrogel beads in water environments. The high specific surface area and porous structure of the hydrogel are conducive to the absorption of a large number of pollutants. The addition of nanomaterials to hydrogels can improve the mechanical strength, swelling behavior, thermal properties and pollutant removal ability of the synthesized hydrogel composites.

[0086] Nano-TiO2 is an inert chemical material with low toxicity and contains many hydroxyl groups. Its high specific surface area and surface activity make it an effective adsorbent, increasing the available absorption sites of the hydrogel system and showing great application potential in wastewater treatment. Under ultraviolet irradiation, the cavities generated on the surface of nano-TiO2 can oxidize water molecules or hydroxide ions to produce strong oxidizing hydroxyl radicals (-OH) and reactive oxygen species. These free radicals can oxidatively degrade organic pollutants in water into harmless carbon dioxide and water, while reactive oxygen species can destroy the cell structure of bacteria and cause cell death, thereby producing an antibacterial effect. In addition, it is also challenging to recover nano-TiO2 in powder form after water treatment. Encapsulating nano-TiO2 in a biopolymer matrix can make it easier to recycle.

[0087] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A microbial composite hydrogel, characterized in that: According to weight parts, it includes: 1-3 parts of polyvinyl alcohol, 3-8 parts of polyethylene glycol, 2-6 parts of sodium alginate, 0.05-0.08 parts of nano titanium dioxide, 10-25 parts of CaCl2, 10-25 parts of boric acid, 5-15 parts of potassium persulfate and Bacillus velezensis, and the concentration of Bacillus velezensis is 0.35*10 8 -0.6*10 8 cells / mL.

2. The microbial composite hydrogel according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 2000-6000; the molecular weight of the polyvinyl alcohol is 20,000-40,000.

3. The microbial composite hydrogel according to claim 1, characterized in that: The nano titanium dioxide is 0.07-0.08 parts.

4. The microbial composite hydrogel according to any one of claims 1 to 3, characterized in that: The particle size of the nano titanium dioxide is 70-80nm.

5. A method for preparing the microbial composite hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, polyvinyl alcohol, polyethylene glycol, sodium alginate, nano titanium dioxide and deionized water are mixed, stirred evenly at 900-100° C., and cooled to obtain a mixed solution 1; S2, mixing CaCl2, boric acid and potassium persulfate uniformly to obtain a mixed solution 2; S3, dropping the mixed solution 1 into the mixed solution 2 for chemical cross-linking, letting it stand for 6-18 hours after the dropwise addition, then washing with water, freeze-drying, and preparing hydrogel microspheres; S4. Mix the hydrogel microspheres and the Bacillus Velez suspension, and culture them at 35-38° C. and 150-220 rpm for 3-6 hours to obtain the microbial composite hydrogel.

6. The method according to claim 5, characterized in that The particle size of the hydrogel microspheres is 2-5 mm.

7. The method according to claim 5, characterized in that In the microbial composite hydrogel, the hydrogel microspheres are loaded with 35-60% of the bacteria in the Velez Bacillus suspension.

8. Use of the microbial composite hydrogel according to any one of claims 1 to 4 in removing COD, TP and / or tetracycline from wastewater.

9. The use according to claim 8, characterized in that: The wastewater is food wastewater.

10. Use of the microbial composite hydrogel according to any one of claims 1 to 4 in inhibiting microorganisms in wastewater.

Citation Information

Patent Citations

  • Selective bactericide with composite nanoparticles as well as preparation and application thereof

    CN102210324A

  • Immobilized microbial preparation and method of treating meat product processing waste water by utilizing same

    CN103205412A

  • Preparation method of granular gel microcarrier for escherichia coli culture

    CN116426516A

  • Preparation method and application of oxygen-carrying negative bacteria immobilized microspheres

    CN117143854A

  • Filamentous algae inhibitor as well as preparation method and application thereof

    CN118415186A

Cited By

  • Periphyton carrier for enriching and killing viruses in aquaculture tail water and preparation method of periphyton carrier

    CN120288905A